VISIBILITAS KEPEMIMPINAN PENDIDIKAN BERBASIS EKOTEOLOGI DI ERA DIGITAL - Siswadi, Siswadi; Afandi, Rahman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the visibility of educational leadership that integrates ecotheological values with the demands of the digital era within the framework of strengthening an organizational culture of quality. The current global environmental crisis is viewed not merely as a technical problem but as a moral and spiritual crisis of modern humanity trapped in an anthropocentric worldview. Using a descriptive qualitative method through a library research approach, this study explores how educational leaders utilize digital technology to transform theological discourse into concrete actions for environmental conservation. The results indicate that the visibility of ecotheological leadership in the digital era can be optimized through three main strategies: (1) the utilization of digital leadership as an instrument for communicating values through e-learning platforms, interactive simulations, and social media to build an environmentally conscious institutional image; (2) the implementation of an integrative curriculum and eco-prophetic education that connects spiritual responsibility with twenty-first-century skills such as STEM and digital literacy; and (3) the application of an inclusive transformational leadership model, including strengthening the role of women’s leadership, which tends to be more collaborative and participatory in fostering an ecological quality culture. In conclusion, the synergy between eschatological awareness and proactive digital innovation becomes a key factor for educational leaders to carry out their role as khalifah in maintaining the balance between humans, nature, and God amid global disruption.